The Influence of Green Human Capital and Green Abilities on Employee Green Behavior with Moderating Role of Green Knowledge Sharing: A Conceptual Study - Ahmed, Laila; Nasir, Aemin; Nasir, Anam; Bakhtawar , Ayesha (South Asian Journal of Social Sciences and Humanities, 2021)
Green human resource management considers the environmental affairs that contribute social and economical well-being of firms and employees. The implementation of green HR practices has been observed in developed countries as scholars and practitioners focused on the environmental concerns. The current conceptual paper is an attempt to investigate the role of green abilities and green human capital to predict the employee’s green behavior. The prime concern of the current study is to analyze the literature of green human resource management and practices that influence the green behavior of employees. The research concludes that green abilities can be generated through effective green training and development approach, the green human capital can be acquired through effective green recruitment and selection procedure. The green knowledge sharing expected to moderate by strengthening the relationship between green human capital and green abilities to explain the employee green behavior.